Microbial Communities and Physicochemical Characteristics of Traditional Dajiang and Sufu in North China Revealed by High-Throughput Sequencing of 16S rRNA - Liang, Tingting; Xie, Xinqiang; Ma, Jun; Wu, Lei; Xi, Yu; Zhao, Hui; Li, Longyan; Li, Haixin; Feng, Ying; Xue, Liang; Chen, Moutong; Chen, Xuefeng; et al. (Frontiers in Microbiology, 2021)
The process of soybean fermentation has been practiced for more than 3,000 years. Although Dajiang and Sufu are two popular fermented soybean products consumed in North China, limited information is available regarding their microbial composition. Hence, the current study sought to investigate, and compare, the physicochemical indicators and microbial communities of traditional Dajiang and Sufu. Results showed that the titratable acidity (TA), and salinity, as well as the lactic acid, and malic acid contents were significantly higher in Sufu samples compared to Dajiang. Furthermore, Sufu samples contain abundant sucrose and fructose, while the acetic acid content was lower in Sufu compared to Dajiang samples. Moreover, the predominant bacterial phyla in Dajiang and Sufu samples were Firmicutes and Proteobacteria, while the major genera comprise Bacillus, Lactobacillus, Tetragenococcus, and Weissella. Moreover, Dajiang samples also contained abundant Pseudomonas, and Brevundimonas spp., while Halomonas, Staphylococcus, Lysinibacillus, Enterobacter, Streptococcus, Acinetobacter, and Halanaerobium spp. were abundant in Sufu samples. At the species level, Bacillus velezensis, Tetragenococcus halophilus, Lactobacillus rennini, Weissella cibaria, Weissella viridescens, Pseudomonas brenneri, and Lactobacillus acidipiscis represented the major species in Dajiang, while Halomonas sp., Staphylococcus equorum, and Halanaerobium praevalens were the predominant species in Sufu. Acetic acid and sucrose were found to be the primary major physicochemical factor influencing the bacterial communities in Dajiang and Sufu, respectively. Furthermore, Bacillus subtilis is strongly correlated with lactic acid levels, Lactobacillus acidipiscis is positively correlated with acetic acid levels, while Staphylococcus sciuri and Staphylococcus equorum are strongly, and positively, correlated with malic acid. Following analysis of carbohydrate and amino acid metabolism in all samples, cysteine and methionine metabolism, as well as fatty acid biosynthesis-related genes are upregulated in Dajiang compared to Sufu samples. However, such as the Staphylococcus, Weissella viridescens, and Pseudomonas brenneri, as potentially foodborne pathogens, existed in Dajang and Sufu samples. Cumulatively, these results suggested that Dajiang and Sufu have unique bacterial communities that influence their specific characteristics. Hence, the current study provides insights into the microbial community composition in Dajiang and Sufu samples, which may facilitate the isolation of functional bacterial species suitable for Dajiang and Sufu production, thus improving their production efficiency.